Step-by-step explanation:
We have
[tex] \frac{20x + 9}{25 {x}^{2} + 20x + 4 } [/tex]
Let's factor the denomiator first,
the denomaitor is a perfect square so we get
[tex] \frac{20x + 9}{(5x + 2) {}^{2} } [/tex]
Now, we must think of two fractions that
[tex] \frac{a}{(5x + 2) {}^{2} } + \frac{b}{5x + 2} [/tex]
We use a perfect square term for one fraction, then a linear one for the next, because if we set both of the denomiator to the same factor, we would get a inconsistent system.
So right now, we have
[tex] \frac{a}{(5x + 2) { }^{2} } + \frac{b}{5x + 2} = \frac{20x +9 }{25 {x}^{2} + 20x + 4 } [/tex]
[tex]a + (5x + 2)b = 20x + 9[/tex]
[tex]5b (x)= 20[/tex]
[tex]a + 2b = 9[/tex]
[tex]b = 4[/tex]
so that means that a is
[tex]a + (2)(4) = 9[/tex]
[tex]a + 8 = 9[/tex]
[tex]a = 1[/tex]
So our equation is
[tex] \frac{1}{(5x + 2) {}^{2} } + \frac{4}{5x + 2} [/tex]